The changing burden of gout in adults aged 70 and above based on the global burden of disease 2019 - Yang, Yang; Liu, Zhong (Frontiers in Public Health, 2025)
IntroductionGout is a significant global health issue, particularly among adults aged 70 and above. Understanding its epidemiological evolution and associated factors is crucial for guiding interventions and improving management.MethodsThis study analyzed data from the Global Burden of Disease study to assess the prevalence and trends of gout among adults aged 70 and above from 1990 to 2019. We evaluated temporal trends and regional disparities by calculating the estimated annual percentage change (EAPCs).ResultsGlobally, the number of older adults individuals affected by gout increased from 5,316,210 cases in 1990 to 15,666,063 cases in 2019. It is noteworthy that the global burden of gout among the older adults continued to rise from 1990 to 2019, with an EAPC of 1.17 (95% CI: 1.02 to 1.32). In 2019, the prevalence rates among individuals aged 70–74, 75–79, 80–84, and 85 and above were 3,121.31 per 100,000, 3,437.17 per 100,000, 3,592.38 per 100,000, and 3,726.91 per 100,000, respectively. The regions with the highest prevalence rates of gout in 2019 were Australasia, High-income North America, and Southern Latin America, with rates of 8,500.73, 8,351.33, and 4,666.87 per 100,000, respectively. At the national level, some developed countries such as New Zealand, the United States of America, and Australia had the highest prevalence rates, reaching 8,893.74, 8,508.06, and 8,427.94 per 100,000, respectively. It is noteworthy that regions with higher levels of Socio-Demographic Index tended to have relatively higher burden of gout among the older adults, and the prevalence rates varied across different regions and age groups.ConclusionThe study underscores the persistent burden of gout among the older adults, emphasizing the need for targeted interventions to address this issue and improve public health outcomes in this demographic.